PENGARUH TINGKAT MELEK HURUF TERHADAP KEMISKINAN DI PROVINSI JAWA BARAT TAHUN 2021-2022 - Lestari, Anita; Ahmadi, Slamet (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The research utilizes data sourced from Central Bureau of Statistics in Indonesia covering the years 2021-2022 for each district in West Java. The dataset includes variables such as Literacy Rates and Number of Poor People, comprising a total of 108 data points across 27 districts. This quantitative approach aims to investigate the interplay between Literacy Rates and poverty using the Structural Equation Modeling method with Partial Least Squares (SEM-PLS) in SmartPLS 4. The study seeks to provide insights into how changes in Literacy Rates influence poverty dynamics within the province. The research finds a significant negative relationship (-0.299) between Literacy Rate and the Number of Poor People. This indicates that as Literacy Rate increases, there is a corresponding decrease in poverty levels within the province. The findings underscore the critical role of literacy in socio-economic development, highlighting its impact on educational attainment, economic opportunities, health outcomes, and community engagement.